2020
DOI: 10.1001/jama.2020.11119
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Hypertension in Children and Adolescents

Abstract: ImportanceChildhood hypertension can result in adverse outcomes during adulthood; identifying and treating primary and secondary childhood hypertension may reduce such risks.ObjectiveTo update the evidence on screening and treatment of hypertension in childhood and adolescence for the US Preventive Services Task Force.Data SourcesPubMed, Cochrane Library, International Pharmaceutical Abstracts, EMBASE, and trial registries through September 3, 2019; bibliographies from retrieved articles, experts, and surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 67 publications
(255 reference statements)
0
14
0
2
Order By: Relevance
“…Currently, hypertension remains an important cause of morbidity and mortality of global population (1), particularly for people from the developing countries (2). Early identification of population at higher risk for the development of hypertension is critical to reduce the incidence of the disease and its cardiovascular complications (3). Previous studies showed that insulin resistance may be involved in the pathogenesis of hypertension via mediating low-degree systematic inflammation (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hypertension remains an important cause of morbidity and mortality of global population (1), particularly for people from the developing countries (2). Early identification of population at higher risk for the development of hypertension is critical to reduce the incidence of the disease and its cardiovascular complications (3). Previous studies showed that insulin resistance may be involved in the pathogenesis of hypertension via mediating low-degree systematic inflammation (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Лечение аторвастатином значительно снижало сывороточные уровни miR-122. В течение 15 лет люди с более высоким уровнем miR-122 на исходном уровне были подвержены повышенному риску развития метаболического синдрома или СД 2 типа [16]. В другой группе пациентов до развития СД , miR-192 и miR-193b положительно коррелировали с триглицеридами в сыворотке крови.…”
Section: использование Microrna как биомаркер сд 2 типа и преддиабетаunclassified
“…В педиатрии эта проблема остается одной из приоритетных, что связано с распространенностью АГ в детской популяции [1,3,6,15] и высокой вероятностью ее трансформации в ишемическую и гипертоническую болезни взрослых [2,5,7,10,14]. АГ среди детей и подростков наблюдается в зависимости от возраста и избранных критериев у 2,4-18% [9,11,16,17]. Вариабельность результатов эпидемиологических исследований в РФ может быть обусловлена климато-географическими, экологическими и этническими особенностями, а также различиями возрастно-половых групп обследуемых [4,8,12,13].…”
Section: заключениеunclassified
“…The USPSTF commissioned a systematic evidence review to update its 2013 recommendation on screening for high blood pressure in children and adolescents . The USPSTF reviewed the evidence on the benefits of screening, test accuracy, the effectiveness and harms of treatment, and the association between hypertension and markers of cardiovascular disease in childhood and adulthood.…”
Section: Update Of Previous Uspstf Recommendationmentioning
confidence: 99%